Penguatan Literasi Bahasa Arab Santri: Program Pengabdian Masyarakat Berbasis Kegiatan Ekstrakurikuler di Pondok Pesantren An Nahdlah Makassar - Harisah, Afifuddin; Pallawagau, Baso; Nuur, Khaerun Nisa; Harjum, Mohamad; Saleh, Muhammad; Gaffar , Nurkhalis A.; Rahman, Anwar Abd.; Wahyudi, Awal (Dedication : Jurnal Pengabdian Masyarakat, 2026)
Arabic language education at the An Nahdlah Islamic Boarding School in Makassar faces challenges in improving the Arabic language literacy of students, particularly in speaking and writing skills. This community service program aims to strengthen Arabic literacy thru extracurricular activities based on direct practice and experience. The program implementation methods include interactive training, thematic discussions, the use of digital learning applications, and the strengthening of teaching methods for instructors. The evaluation results showed a significant improvement in the students' Arabic language skills, with 75% of the students feeling more confident in using Arabic after attending the training. Additionally, this program successfully created a supportive learning community, increased social interaction among students, and produced learning modules that can be used for Arabic language instruction in other pesantren. This program not only enhances Arabic language skills but also builds the character and self-confidence of the students as part of their identity.